Paget’s Breast Disease: A Case Report and Review of the Literature - Dubar, S.; Boukrid, M.; Bouquet de Joliniere, Jean; Guillou, L.; Vo, Quoc Duy; Major, A.; Ali, N. Ben; Khomsi, F.; Feki, A. (Frontiers in Surgery, 2017)
Paget's disease of the breast is a rare cancer. This typical clinical case illustrates the different epidemiological, clinical, histological, therapeutic and evolving aspects of the disease. We report a case of Paget’s disease in a 43-years-old woman who presented eczema of the nipple. Mammography and ultrasounds did reveal a lesion in situ. The patient was scheduled for mastectomy and sentinel node biopsy. She had chosen a radical bilateral surgery. The histological diagnosis was Paget's disease of the breast with a carcinoma in situ. There was no metastasis in either of the sentinel nodes. Paget's disease must be considered with the presence of eczematous involvement of the persistent nipple, which does not respond to local treatment. Ultrasounds, mammography and MRI can allow searching an underlying cancer and guiding the surgical management. There is no evidence at this time that one of the 2 surgical techniques (conservative or mastectomy) would improve survival. The prognosis depends on the presence of a palpable mass and the invasiveness of the cancer